Dimensi Teologi dalam Ritual Sedekah Bumi Masyarakat Made - Hassan Nugroho (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2018)
This study discusses the phenomenon of tradisi sedekah bumi (giving alms to the mother Earth) in the Village of Made, Sambikerep, Surabaya. The tradition of giving alms to the mother Earth –which has been commonly performed by agrarian society (rural people) in Java as a manifestation of thankfulness upon